Synthesis, Characterization, Thermal Behavior, and Dielectric Properties of Methacrylate Polymers Containing Imine Bonding - Solmaz, Adnan; Ilter, Zulfiye; Kaya, Ismet (Springer, 2021)
Two different Schiff bases, viz. 1-{4-[(5-bromo-2-hydroxybenzyliden)amino]phenyl}ethanone (5-Br-2HBAPE) and 1-{4-[(4-hydroxybenzylidene)amino]phenyl}ethanone (4-HBAPE), have been prepared by condensation of 5-bromosalicylaldehyde and 4-hydroxybenzaldehyde with 4-aminoacetophenone in ethanol at molar ratio of 1:1. Then, Schiff base methacrylate monomers, i.e., 2-(((4-acetylphenyl)imino)methyl)-4-bromophenylmethacrylate (APIMBPM) and 2-(((4-acetylphenyl)imino)methyl)phenylmethacrylate (APIMPM), were synthesized by reaction of each Schiff base compound with methacryloylchloride at 0 degrees C to 5 degrees C. Schiff base methacrylate polymers poly(APIMBPM) and poly(APIMPM) were then prepared by free-radical polymerization in tetrahydrofuran (THF) at 70 degrees C using azobisisobutyronitrile (AIBN) as initiator. The structure of 5-Br-2HBAPE, 4-HBAPE, APIMBPM, APIMPM, poly(APIMBPM), and poly(APIMPM) was confirmed by Fourier-transform infrared (FT-IR) and H-1 and C-13 nuclear magnetic resonance (NMR) spectroscopy. The thermal behavior of poly(APIMBPM) and poly(APIMPM) was studied by differential scanning calorimetry (DSC) and thermogravimetry (TG). The glass-transition temperature (T-g) of poly(APIMBPM) and poly(APIMPM) was found to be 113 degrees C and 108 degrees C, respectively. The residual amount of poly(APIMBPM) and poly(APIMPM) at 1000 degrees C was found to be 45.60% and 26.35%, respectively. Dielectric and conductivity measurements were carried out on the Schiff base methacrylate polymers by impedance analysis as a function of frequency. The conductivity of poly(APIMBPM) and poly(APIMPM) was found to be 1.30 x 10(-9) S cm(-1) and 2.14 x 10(-9) S cm(-1), respectively. Scanning electron microscopy (SEM) was used to investigate the morphology of the Schiff base methacrylate polymers, and their antimicrobial activity against bacteria and fungus was determined by disk diffusion method. Poly(APIMBPM) exhibited good antibacterial property against Klebsiella pneumonia. Poly(APIMBPM) and poly(APIMPM) exhibited good antifungal action against Candida albicans. We thus describe the synthesis of different Schiff base methacrylate polymers and their thermal behavior, electrical properties, and antimicrobial activities.
Keywords: Free radical polymerization; Schiff base polymer; thermal properties; dielectric features; antibacterial activity; antifungal activity